20-3+10=27
ответ:1) 27
1) 2^8+4^5-8^2=2^8+(2^2)^5-(2^3)^2=2^8+2^10-2^6=2^6*(2^2+2^4-1)=2^6*(4+16-1)=2^6*19=2^5*(2*19)=2^5*38 это выражение делится на 38
(2^5*38)/38=2^5=32 что требовалось доказать
2) 3^11+9^6+27^3=3^11+(3^2)^6+(3^3)^3=3^11+3^12+3^9=3^9*(3^2+3^3+1)=3^9*(9+27+1)=3^9*37=3^8*(3*37)=3^8*111 это выражение делится на 111
(3^8*111)/111=3^8 что требовалось доказать
3) a=9^7+9^6+9^5=(3^2)^7+(3^2)^6+(3^2)^5=3^14+3^12+3^10=3^10*(3^4+3^2+1)=3^10*(81+9+1)=3^10*91.
b=3^10-3^9+3^8=3^8*(3^2-3+1)=3^8*(9-3+1)=3^8*7
(3^10*91)/(3^8*7)=3^2*91/7=9*13=117 что и требовалось доказать а делится на bВідповідь:
19x-11y+12=0
Покрокове пояснення:Simplifying
19x + -11y + 12 = 0
Reorder the terms:
12 + 19x + -11y = 0
Solving
12 + 19x + -11y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + 19x + -12 + -11y = 0 + -12
Reorder the terms:
12 + -12 + 19x + -11y = 0 + -12
Combine like terms: 12 + -12 = 0
0 + 19x + -11y = 0 + -12
19x + -11y = 0 + -12
Combine like terms: 0 + -12 = -12
19x + -11y = -12
Add '11y' to each side of the equation.
19x + -11y + 11y = -12 + 11y
Combine like terms: -11y + 11y = 0
19x + 0 = -12 + 11y
19x = -12 + 11y
Divide each side by '19'.
x = -0.6315789474 + 0.5789473684y
Simplifying
x = -0.6315789474 + 0.5789473684y
20-15:5+10=20-3+10=27
ответ: 27 под цифрой 1